Genetic variability between populations of the critically endangered frog Microbatrachella capensis, Boulenger 1910 (Anura: Ranidae: Cacosterninae) - Kryger, Ute (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2005.